2012
DOI: 10.1093/hmg/ddr614
|View full text |Cite
|
Sign up to set email alerts
|

Defective glucocorticoid hormone receptor signaling leads to increased stress and anxiety in a mouse model of Angelman syndrome

Abstract: Angelman syndrome (AS) is a neurodevelopmental disorder caused due to deletions or loss-of-function mutations in maternally inherited UBE3A. Ube3a functions as an ubiquitin ligase as well as a transcriptional coactivator of steroid hormone receptors. However, the mechanisms by which maternal Ube3a deficiency gives rise to phenotypic features of AS are not clear. We report here that Ube3a regulates glucocorticoid receptor (GR) transactivation and GR signaling pathway is disrupted in Ube3a-maternal-deficient mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 53 publications
6
35
1
3
Order By: Relevance
“…Acute and chronic treatment of corticosterone in mice also leads to decrease in neurogenesis [32]. Recently, we have shown disrupted GR signalling in the hippocampus of AS mice brain [26]. These mice also show elevated serum corticosterone levels and exhibits anxiety-like behaviour that can be partially restored upon chronic treatment of fluoxetine [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute and chronic treatment of corticosterone in mice also leads to decrease in neurogenesis [32]. Recently, we have shown disrupted GR signalling in the hippocampus of AS mice brain [26]. These mice also show elevated serum corticosterone levels and exhibits anxiety-like behaviour that can be partially restored upon chronic treatment of fluoxetine [27].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that adult neurogenesis in the hippocampal DG region modulates hippocampal functions, especially hippocampaldependent learning and memory [18,20,21] and impaired neurogenesis in this region have been implicated in the number of cognitive and psychiatric disorders as well as under chronic stress conditions [19,22e25]. Recently, we have demonstrated that AS mice are under chronic stress and exhibits anxiety-like behaviour due to defective glucocorticoid receptor (GR) signalling and such abnormalities can be partially rescued upon chronic treatment of fluoxetine [26,27]. Here we studied neurogenesis in both hippocampal DG and SVZ regions of AS mice along with wild type controls from early postnatal days to adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of the ubiquitin-mediating gene ubiquitin protein ligase E3A (Ube3a), which encodes the protein involved in targeting proteins for their multi-ubiquitylation, has also been shown to decrease neuronal differentiation during adult neurogenesis, although the mechanism remains unknown 66 . However, another study showed that dysfunction of UBE3A decreased ubiquitin-mediated glucocorticoid receptor degradation and that this may be the mechanism through which such dysfunction induces an anxiety-like phenotype 67 ; in turn, anxiety-like phenotypes have been associated with a decrease in adult neurogenesis. These studies indicate that ubiquitylation may be important in the regulation of both stress and adult neurogenesis.…”
Section: Subventricular Zonementioning
confidence: 99%
“…Depending on the strain and reporting laboratory, Ube3a m-/p+ mice may show a deficit in water-maze acquisition, testing, or reversal training [35,36,38,42]. Anxiety phenotypes are reported, as shown by dark preferences in light-dark tests and lack of novel object preference, as well as preference for edges and increased freezing in open field-testing [38,43]. Mice with AS bury fewer marbles than their wild-type controls [38].…”
Section: As Mouse Modelsmentioning
confidence: 99%